Ungheria 1945-2002. La dimensione letteraria - Tottossy, Beatrice (Biblioteca di Studi di Filologia Moderna, 2012)
The 2002 Nobel Prize to Imre Kertész is a symptom: Hungary is now weltliterarisch. The historical process - which has seen Hungarian writers working since the 1970s to gain ontological autonomy for their field, to write in a language that is not mendacious, to go beyond the 'modern' of real socialism to a 'postmodern' in which reality is not "described", but "employed", and to anthropic ends - is at a standstill, it is greeted abroad as a common heritage. According to Ungheria 1945-2002. La dimensione letteraria - which concludes a prolonged period of analytical work (see Scrivere postmoderno in Ungheria, 1995, and Scrittori ungheresi allo specchio, 2003) - the Hungarian contribution to the contemporary era lies in its sense for this anthropic function of literature (even though the context now seems to want to thwart this effort).